2018
DOI: 10.12973/ijem.4.3.125
|View full text |Cite
|
Sign up to set email alerts
|

The Promising Roles of Augmented Reality in Educational Setting: A Review of the Literature

Abstract: This present study imparts a literature review focusing on Augmented Reality (AR) in the field of education. The writers reviewed the published manuscripts by centering on types of manuscripts, research designs, types of participants, and the promising roles of AR in educational setting. A total number of 18 articles were thoroughly analyzed. The results showed a diverse type of manuscripts published in the journal databases including research articles, reviews, technical notes, features, and news. Types of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This has led a small number of researchers to explore the role of AR applications in enhancing the learning of students with special needs (Sırakaya & Alsancak Sırakaya, 2018;Yuliono & Rintayati, 2018). For example, through a meta-analysis study, Barton, Pustejovsky, Maggin, and Reichow (2017) confirmed the effectiveness of technology-aided instructions in facilitating the integration of students with autism spectrum disorder (ASD) into the community.…”
Section: Introductionmentioning
confidence: 99%
“…This has led a small number of researchers to explore the role of AR applications in enhancing the learning of students with special needs (Sırakaya & Alsancak Sırakaya, 2018;Yuliono & Rintayati, 2018). For example, through a meta-analysis study, Barton, Pustejovsky, Maggin, and Reichow (2017) confirmed the effectiveness of technology-aided instructions in facilitating the integration of students with autism spectrum disorder (ASD) into the community.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of literature on AR application in special education revealed AR's role in supporting learning among individuals with disabilities in terms of self-determination and self-management, self-instruction guidance in the resolution of complex tasks, and guidance to different environments (Gomez-Puerta et al, 2019). AR technology may also be useful in improving special needs students' learning (Sirakaya & Sirakaya, 2018;Yuliono & Rintayati, 2018). Studies along this line include Benda et al (2015) and Smith et al (2015) study's that supported the great potential effect of augmented reality technology on display educational materials that proven to be great tool to improved experience in learning such as navigation skills among adult with intellectual disability.…”
Section: Augmented Reality In Special Education In Higher Education Settingmentioning
confidence: 99%
“…AR is able to improve students' understanding of the material [39], [40]. Therefore, the utilize of AR in the learning process can lead the improvement of students' learning outcomes [28], [40].…”
Section: Improving Students' Understandingmentioning
confidence: 99%
“…AR technology in the learning environment has a positive impact on students' motivation [19], [30], [39], [43]. AR is an interactive learning media that can increase students' interest, concentration and satisfaction with the use of new technology in learning [42].…”
Section: Increasing Students' Motivationmentioning
confidence: 99%